1993
DOI: 10.1111/j.1365-2621.1993.tb03219.x
|View full text |Cite
|
Sign up to set email alerts
|

Minced Meat Crabcake from Blue Crab Processing Byproducts—Development and Sensory Evaluation

Abstract: Quantitative and qualitative characteristics of minced meat, mechanically separated from blue crab processing by-product, were determined. Sensory evaluation was performed on crabcakes with various combinations of claw mince/meat (CMM), surimi, and functional soy protein concentrate (SPC). Separation produced 50-58% food-grade mince from picking table by-products and 49% from undersized claws. Claw mince had lower microbial concentrations than the composite picking table by-products. Crabby and beany flavors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…Pasteurization of the minced meat and addition of citric acid–phosphate buffer improved appearance and controlled microbial levels. In another study, minced meat from undersized blue crab claw was combined with picked claw meat, 10% pollock surimi ( Theragra chalcogramma ), and 30% to 50% soy protein concentrate to produce a crabcake acceptable to consumers (Lee and others 1993). Additional research that focuses on the use of crab mince as the primary component of value‐added products is needed to increase utilization of this resource.…”
Section: Introductionmentioning
confidence: 99%
“…Pasteurization of the minced meat and addition of citric acid–phosphate buffer improved appearance and controlled microbial levels. In another study, minced meat from undersized blue crab claw was combined with picked claw meat, 10% pollock surimi ( Theragra chalcogramma ), and 30% to 50% soy protein concentrate to produce a crabcake acceptable to consumers (Lee and others 1993). Additional research that focuses on the use of crab mince as the primary component of value‐added products is needed to increase utilization of this resource.…”
Section: Introductionmentioning
confidence: 99%
“…Chung and Cadwallader (1993) compared volatile components of blue crab meat and processing by-product and concluded that the by-product had significantly higher concentrations of volatile compounds. In a related study, mechanically-separated minces from blue crab undersized claws were utilized for value-added crabcake products (Lee et al, 1993). Incorporation of proteolytic enzymes from fish or crustacean viscera may improve the extraction of flavor compounds (Haard, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Minerals constitute important components of hormones, enzymes and enzyme activators in human nutrition (Kirtpatrick and Coffin, 1974; Khan et al, 1987;Lall, 1989Lall, , 1995. Food source and environmental factors affect minerals content (Anthony et al, 1983;King et al, 1990; Lee et al, 1993;Skonberg and Perkins, 2003;Gokoglu and Yerlikaya, 2003;Yannar and Celik, 2006). Mineral components such as sodium, potassium, magnesium, calcium, iron, phosphorus and iodine are important for human nutrition (Sikorski et al, 1990).…”
Section: Introductionmentioning
confidence: 99%